A Systolic Blood Pressure of 100 mm Hg Is Optimal for Optimal Visualization in Arthroscopic Rotator Cuff Repair in the Beach-Chair Position - Megumi Shingu, R.N., M.S; Nariyuki Mura, M.D., Ph.D; Tomohiro Uno, M.D; Ryuta Oishi, M.D; Tadashi Koseki, O.T; Kaori Sakurada, M.D., Ph.D (Elsevier, 2021)
Purpose: To investigate the relationship between visualization and blood pressure during arthroscopic rotator cuff repair (ARCR) in the beach-chair position and to clarify the optimal blood pressure to maintain good visualization during surgery. Methods: One senior surgeon evaluated intraoperative visualization at the start of arthroscopy, at acromioplasty, at the refresh of the footprint on the greater tuberosity, at marrow vent creation in the footprint on the greater tuberosity, and at rotator cuff fixation. The evaluation grades were: 5, clear; 4, mild bleeding; 3, bleeding but operable; 2, poor visualization due to bleeding; and 1, inability to continue surgery due to massive bleeding. During ARCR, an arterial line was inserted, and blood pressure was measured continuously. The relationship between visualization and blood pressure was analyzed. Receiver operating characteristic analysis was performed with evaluation grades 5 and 4 as the good visualization group and the other evaluation grades as the poor visualization group. Results: Visualization assessment and systolic/diastolic blood pressure were associated at the start of arthroscopy (P = .0257/.0057), at acromioplasty (P = .0023/.0399), and at the refresh of the footprint (P = .0201/.0272). The average blood pressure of evaluation grade 5 cases was 91/50 mm Hg. The cut-off values, based on the area under the curve on receiver operating characteristic analysis, were as follows: 104/60 mm Hg (0.91-0.95) at acromioplasty; 116/70 (0.94-0.96) at the refresh of the footprint; 116/70 mm Hg (0.94-0.96) at the refresh of the footprint; and 106/58 mm Hg (0.73-0.70) at marrow vent creation. Conclusions: Good visualization during ARCR in the beach-chair position was significantly associated with blood pressure. An optimal blood pressure resulting in good visualization that would not cause excessive hypotension during ARCR surgery in the beach-chair position might be a systolic blood pressure of 100 mm Hg. Level of Evidence: III, prospective, nonrandomized, observational study.